The Soybean Through World History : Lessons for Sustainable Agrofood Systems. - Baraibar Norberg, Matilda. (Routledge Studies in Food, Society and the Environment Series, 2023)
This book examines the changing roles and functions of the soybean throughout world history and discusses how this reflects the complex processes of agrofood globalization.